Lift your impact transform your mindset, influence and future to elevate your work, team, and life - Newman, Richard 1977- (McGraw-Hill, 2023)
"Richard Newman's research into non-verbal communication and influence revealed something groundbreaking: small changes in how you communicate can create a massive difference in the way you are perceived by those around you"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 20, 2023)
Keywords: Attitude (Psychology); Body language; Social interaction; Success; Self-realization; Attitude (Psychologie); Langage du corps; Interaction sociale; Succès; Réalisation de soi